Fitter Mitochondria Are Associated With Radioresistance in Human Head and Neck SQD9 Cancer Cells - Grasso, Debora; Medeiros, Hyllana C. D.; Zampieri, Luca X.; Bol, Vanesa; Danhier, Pierre; van Gisbergen, Marike W.; Bouzin, Caroline; Brusa, Davide; Grégoire, Vincent; Smeets, Hubert; Stassen, Alphons P. M.; Dubois, Ludwig J.; et al. (Frontiers in Pharmacology, 2020)
The clinical management of head and neck squamous cell carcinoma (HNSCC) commonly involves chemoradiotherapy, but recurrences often occur that are associated with radioresistance. Using human SQD9 laryngeal squamous cell carcinoma cancer cells as a model, we aimed to identify metabolic changes associated with acquired radioresistance. In a top-down approach, matched radiosensitive and radioresistant SQD9 cells were generated and metabolically compared, focusing on glycolysis, oxidative phosphorylation (OXPHOS) and ROS production. The cell cycle, clonogenicity, tumor growth in mice and DNA damage-repair were assessed. Mitochondrial DNA (mtDNA) was sequenced. In a bottom-up approach, matched glycolytic and oxidative SQD9 cells were generated using FACS-sorting, and tested for their radiosensitivity/radioresistance. We found that acquired radioresistance is associated with a shift from a glycolytic to a more oxidative metabolism in SQD9 cells. The opposite was also true, as the most oxidative fraction isolated from SQD9 wild-type cells was also more radioresistant than the most glycolytic fraction. However, neither reduced hexokinase expression nor OXPHOS were directly responsible for the radioresistant phenotype. Radiosensitive and radioresistant cells had similar proliferation rates and were equally efficient for ATP production. They were equally sensitive to redox stress and had similar DNA damage repair, but radioresistant cells had an increased number of mitochondria and a higher mtDNA content. Thus, an oxidative switch is associated with but is not responsible for acquired radioresistance in human SQD9 cells. In radioresistant cells, more and fitter mitochondria could help to preserve mitochondrial functions upon irradiation.